Powtoon as Digital Learning Media in Academic Writing Class: Students’ Perspective and Challenges - Indriani, Lilia; Ekaningrum, Rini Estiyowati; Rahardi, Panggih (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2023)
Facing the post-Covid-19 pandemic, teachers need to enhance technology in their teaching and learning process, especially in delivering the materials for the students. As digital natives, students are familiar with technology, and it makes them excited in learning English materials. Academic writing materials are complex because it involves expressing ideas carefully elaborated, and well-supported, logically sequenced, rigorously reasoned, and tightly stitched together. Powtoon is one of the solutions to make the materials more interesting and understandable for the students in academic writing class. This study aims to know the students’ perspectives and challenges about the use of Powtoon as digital learning media to improve writing skills. The subjects are 37 students in English Department in one of the state universities in Indonesia. The method is qualitative by using questionnaire, interview, and documentation. It is found that the students have positive perceptions (76.92%) on the use of Powtoon as digital learning media to improve writing skills. Hence, Powtoon is recommended as digital learning media to improve the students’ writing skills. However, the motion of the animation could distract student's concentration in understanding the materials. Apart from that, students still need to ask directly to the teacher if they have not really understood about the materials presented using Powtoon.